Pyrifenox, an ergosterol inhibitor, differentially affects Cryptococcus neoformans and Cryptococcus gattii. (8th January 2020) - Silva, Vanessa K A; May, Robin C; Rodrigues, Marcio L
Abstract: Cryptococcosis is a life-threatening fungal infection. New therapeutic approaches are necessary to combat cryptococcosis, as the currently available therapeutic protocols are expensive and generally result in deleterious side effects. Pyrifenox is an antifungal compound that affects phytopathogens by inhibiting the biosynthesis of ergosterol. In this study, we investigated the effects of pyrifenox on Cryptococcus neoformans and Cryptococcus gattii growth, capsule architecture and export of the major capsule component, glucuroxylomannan (GXM). Pyrifenox inhibited the growth of C. neoformans, but was significantly less effective against C. gattii . The resistance of C. gattii to pyrifenox was associated with the expression of efflux pump genes, particularly AFR1 and AFR2, since mutant cells lacking expression of these genes became sensitive to pyrifenox. Analysis of the cryptococcal capsule by India ink counterstaining, immunofluorescence, and scanning electron microscopy showed that pyrifenox affected capsular dimensions in both species. However, GXM fibers were shorter and uniformly distributed in C. neoformans, whereas in C. gattii the number of fibers was reduced. Pyrifenox-treated C. gattii developed unusually long chains of undivided cells. The secretion of GXM was markedly reduced in both species after treatment with pyrifenox. Altogether, the results indicated that pyrifenox differently affects C. neoformans and C. gattii . In addition, it highlights a potential role for pyrifenox as an inhibitor of GXM export in experimental models involving pathogenic cryptococci.